DESCRIPTIVE STUDY OF TONSILLECTOMY IN PATIENTS AT RS TK III BALADHIKA HUSADA JEMBER FROM 2022 TO 2023 - Fardillah, Nella Nabella; Arianto , Denny Rizaldi (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Tonsillectomy is the most common performed surgical procedure. Over 500,000 cases are performed annually in children under 15 years old. This study was conducted to identify patients undergoing tonsillectomy therapy at RS TK III Baladhika Husada Jember. Methods: A retrospective descriptive study using secondary data with a consecutive sampling method. Results: The total number of patients in this study was 55. The largest group of patients was in the age range of 17-25 years, comprising 40 (72.7%) patients. The most frequent diagnosis indicating the therapy was chronic tonsillitis in 50 (90.9%) patients. The results of this study showed that the longest hospitalization for patients undergoing tonsillectomy was five days, while the shortest was two days. Conclusion: The patients undergoing tonsillectomy at RS Baladhika Husada Jember were predominantly male and aged 17-25 years. The most common diagnosis leading to tonsillectomy was chronic tonsillitis, with the most frequent hospitalization duration being three days.